THE RELATIONSHIP BETWEEN PARENTAL INVOLVEMENT AND STUDENTS’ ACADEMIC ACHIEVEMENT - Nurhayati Nurhayati; Ritly Julia Rondonuwu (Universitas Lampung, 2023)
This study aimed to determine the relationship between parental involvement and students’ academic achievement. In addition, the purpose of this study was to determine the level of parental involvement and student academic achievement. To answer the research questions, descriptive mean analysis and Pearson Product Coefficient Correlation were used. The findings revealed that: (1) the level of parental involvement was 3.82, indicating frequent parental involvement; (2) the level of student academic achievement was 83.07, indicating good academic achievement; and (3) the p =.135 and r =.195, indicating that there is no significant correlation between parental involvement and student academic achievement; however, the correlation was found to be positive but only weakly. The researcher concluded that parental involvement is not a significant factor that has a relationship with student academic achievement. It is suggested that future researchers or teachers look for other factors that have a significant relationship on student academic achievement.Penelitian ini bertujuan untuk mengetahui hubungan keterlibatan orang tua dengan prestasi akademik siswa. Selain itu, tujuan dari penelitian ini juga untuk mengetahui tingkat keterlibatan orang tua serta tingkat prestasi akademik siswa. Untuk menjawab pertanyaan penelitian, digunakan descriptive mean analysis dan Pearson Product Coefficient Correlation. Hasil penelitian menunjukkan bahwa: (1) tingkat keterlibatan orang tua sebesar 3.82, menunjukkan keterlibatan orang tua yang sering dilakukan; (2) tingkat prestasi akademik siswa sebesar 83,07 yang menunjukkan bahwa prestasi akademik siswa adalah baik; dan (3) p=0.135 dan r=0.195, menunjukkan bahwa tidak ada korelasi yang signifikan antara keterlibatan orang tua dengan prestasi akademik siswa. Namun demikian, korelasinya ditemukan positif tetapi lemah. Peneliti menyimpulkan bahwa keterlibatan orang tua bukanlah faktor signifikan yang memiliki hubungan dengan prestasi akademik siswa. Disarankan kepada para peneliti atau guru-guru mendatang untuk meneliti faktor lain yang secara signifikan berpengaruh terhadap prestasi akademik siswa. Keywords: Parental Involvement, Students’ academic achievement.DOI Artikel: https://doi.org/10.23960/J-Simbol/v11i1.2023.06